(untitled) (Medical Forum Monthly, 2024)
Objective: This study has been undertaken to assess the spermatoprotective role of magnesium sulphate (MgSO4) on the histology of the seminiferous tubules in dexamethasone induced spermatogenic cells damage in albino rats. Study Design: Prospective experimental study. Place and Duration of Study: This study was conducted at the Department of Anatomy, Basic Medical Sciences Institute (BMSI), Jinnah Postgraduate Medical Centre (JPMC), Karachi from April 2012 to May 2012. Materials and Methods: Thirty male albino rats of 90-120 days of age and around 200-250 grams of weight were selected and divided into three groups (A, B&C). Each group comprising of ten rats. Group-A served as control, group-B was given dexamethasone (Dexa) at the dose of 4mg/kg/day intraperitoneally for 20 days. Group-C was administered MgSO4 at the dose of 20mg/kg/day intramuscularly and Dexa at the same dose as given in group- B. The rats were sacrificed at the end of the experimental period and histopathological changes in the germ cells were recorded. Results: The microscopic examination of group-B rats revealed marked changes in most of the seminiferous tubules such as, vacuolization, detachment of basement membrane, atrophy, sloughing, widening of the interstitial spaces & disorganization of the spermatogenic cells series. Group-C which was protected with magnesium sulphate, showed restoration of basement membrane and spermatogenic cell series. Conclusion: The present study concluded that magnesium sulphate (MgSO4) administration reduced the damaging effects of dexamethasone in testes.